Effect of industrial transfer on carbon lock-in: a spatial econometric analysis of Chinese cities - Xu, Yingzhi; Dong, Biying; Chen, Yan; Qin, Hanwen (Journal of environmental planning and management, 2022)
To explore the potential effect of industrial transfer on carbon lock-in in China, this paper constructed the measurement formula of industrial transfer based on output and demand, and calculated carbon lock-in according to carbon sink and carbon emissions. By means of a spatial autoregressive model and a panel threshold model, we discussed the spatial spillover of carbon lock-in and the effect of industrial transfer. The findings are as follows: (1) The level of carbon lock-in does have a positive spatial spillover effect between economic neighboring provinces. (2) The effect of industrial transfer on carbon lock-in depends on industry characteristics. (3) Technological progress has direct and indirect carbon unlocking effects, energy structure, trade openness and increased fiscal expenditure exacerbate the carbon lock-in dilemma, while economic growth and carbon lock-in show an inverted "U" relationship. (4) There is a non-linear relationship between industrial transfer and carbon lock-in. Finally, we propose some recommendations to reduce dependence on high-carbon fossil energy and speed up the process of carbon unlocking in China.